Performa Budidaya Ikan Nila Saline (Oreochromis niloticus Salina) Pada Kolam Silvofishery - Heri Ariadi; Hayati Soeprapto; Ana Sulistiana (Faculty of Science and Technology University Ibrahimy, 2024)
Silvofishery is an environmentally friendly cultivation model that is now widely implemented in coastal areas of Indonesia. The aim of this research is to conduct a study on the use of saline tilapia fish (Oreochromis niloticus) as a cultivar in silvofishery cultivation. The research method used is qualitative descriptive research. The parameters studied are water quality and aspects of the financial feasibility of the business. The research results showed that the weight of saline tilapia fish during cultivation ranged from 3.01-21.24 gr (13.37 ± 6.53) and biomass growth was 3,010-19,116 kg (12,886 ± 7.79). Silvofishery water quality parameters produced data: pH 7.8-8.2 (8.0 ± 0.14), dissolved oxygen 4.01-5.92 mg/L (4.90 ± 0.55), temperature 31.00-32,750C (31,800C ± 0.60), salinity 5-8 gr/L ( 6.3 ± 1.28) and organic matter 54.32-73.87 mg/L (62.90 ± 6.33). The financial feasibility value of the business shows a profit value of IDR. 8,840,000,-, R/C Ratio 1.55, BEP unit 297 kg, BEP sales Rp. 4,428,000,-, profitability 25%, Net Present Value Rp. 101,528,000,-, IRR 20.45%, and payback period 2.7 years. Based on the presentation of research data, saline tilapia is highly recommended as a commodity for silvofishery cultivation. The conclusion of this research is that saline tilapia would be ideal to be used as the main commodity in silvofishery cultivation activities carried out in coastal areas.